Science teachers’ perception of the use of educational computer gamers in selected senior high schools in Akwapim North District - Larbi, Abigail (University of Cape Coast, 2020)
Information and Communication Technology (ICT) has become a household name for any country that wants to develop education. ICT has received significant attention from successive governments over the past decade at the senior high school level. Teaching and learning have evolved over the years from the traditional instructivism, to the constructivism approach where learners have become active organism with expectations and the teacher becoming a facilitator. The aim of the study was to investigate the use of ICT as a constructivist approach to the teaching and learning of Physics m Swedru senior high school. The study was underpinned by the constructivist theory. The study adopted a quantitative research approach and descriptive research design. There is no approach like this in the main work and simple random sampling techniques were used in this research The sample size was 206 students who were randomly selected and 8 science teachers who were purposely selected. Questionnaire was used as a research instrument for data collection. Descriptive statistical tools were used in analysing the data. The study revealed that the use of ICT in the teaching and learning of Physics were perceived to develop diverse learning, critical thinking and active student participation which improve student's performance in the subject. It was recommended that, the Government should adopt ICT as a constructivist approach to the teaching and learning of Physics in junior high schools by providing the necessary logistics and infrastructure so that they can use ICT resources to enhance teaching and learning.
viii, 118p :,ill